Identification and Classification of Bus and Subway Passenger Travel Patterns in Beijing Using Transit Smart Card Data. (5th January 2023) - Wang, Lewen; Chen, Yuan; Wang, Yu; Sun, Xiaofei; Wu, Yizheng; Peng, Fei; Song, Guohua
Abstract : Urban public transit has been rapidly developed in recent years. However, given increases in travel volume, the level of service still needs to be improved to meet the satisfaction of passengers. Transit service providers and researchers have focused on improving transit devices, but the service level of public transit has not yet been effectively improved, so more and more research is interested in analyzing the travel patterns of passengers. Compared with traditional survey methods, smart card collection systems—which can collect spatial-temporal information about passengers' trips—are convenient for the study of bus and subway passengers' travel patterns. However, the data provided by smart cards have not yet been fully explored. Therefore, this paper proposed a multistep methodology to gather information on the travel patterns of bus and subway passengers in Beijing, China. We conducted statistical analyses and used an unsupervised clustering method to study and classify passengers based on travel patterns. Four groups have been identified: standard commuters, flexible commuters, and two types of low-frequency passengers. Then, a comprehensive analysis was conducted. We also discussed the changes of passengers' travel time consumption before and after the implementation of customized bus for high-frequency passengers. The analyses indicated that passengers' travel patterns can provide useful information for transit service providers and can help improve the level of service of urban public transit by promoting the promulgation of local public transport policies and the implementation of customized services.